Improvement of myrosinase activity of Aspergillus sp. NR4617 by chemical mutagenesis - Rakariyatham N. (2014)
A myrosinase (thioglucoside glucohydrolase or thioglucosidase, EC 3.2.3.147) producing fungus, Aspergillus sp. NR4617, was newly isolated from decayed soil sample obtained in Thailand and was subjected to single exposure to two chemical mutagens, ethyl methanesulfonate (EMS) and N-methyl-N′- nitro-N-nitrosoguanidine (MNNG). Its myrosinase production was selected on low cost medium prepared from mustard seed cake (Brassica juncea). Studies of production and stability of the enzyme showed that EMS mutagenesis increased myrosinase activity. Aspergillus sp. NR4617E1 produced myrosinase 1.90 U ml -1 at 36 hrs of the cultivation equivalent to 171% of the enzyme production in wild-type. The stability studies revealed that myrosinase from the mutant strains retained activity similar to wild-type at 30°C. Aspergillus sp. NR4617E1 degraded 10 mM of glucosinolate completely in 36 hrs. Enhanced myrosinase production and high yields of products (allylisothiocyanate) demonstrated that this mutant could be a new found candidate for feed detoxification and industrial allylisothiocyanate production. © 2006 by Pontificia Universidad Católica de Valparaíso.